Peran Teknologi Blockchain Untuk Institusi Zakat di Indonesia - Zulfikri Zulfikri (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
Indonesia is one of the most populous Muslim countries in the world but is still plagued with poverty. Zakat is one of the effective tools of Islamic philanthropy to reduce poverty, therefore zakat management is very important for this country so that zakat collection and distribution can be maximized. In today's digital world, it is very important for zakat institutions to use technology so that zakat management performance can be better and more efficient. The technology that stole the world's attention is blockchain technology. Blockchain technology has disrupted the financial sector because it offers transparent transactions so there is no need for intermediaries. This study explains the role of blockchain technology on zakat institutions in Indonesia. The research method used is an extensive literature to identify and analyze the relevant literature. The results of the study show that the role of blockchain technology can improve zakat management, especially on transparency in zakat distribution so that muzakki's trust in zakat institutions is improving.